The Purple Squirrel Paradox: Leveraging Technology and Inclusive Strategies for Attracting and Retaining Exceptional Talent in Tech Startups - Choudhary, Parul; Raja M, Dr Anand Shankar; Kothari, Dr Manish (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
The systemic problem within the tech industry startup surrounds the disparity of talent expectation with reasonable and sustainable employment practices, which is visible through the lens of the Purple Squirrel Paradox - the relentless ideal of the all-in-one, dwarfed. This paper addresses the social impact of paradox-technology and inclusive management in resolving the contradiction of social impact tech paradox. Use of AI-enabled recruitment tools, skills-first assessment of candidates, and proactive outreach campaigns has been shown to reduce bias and improve access to and appreciation of talent that has been previously ignored and underutilized. We also examine retention strategies anchored in psychological safety, equity-centered leadership development, inclusive onboarding, and their long-term social value. This work in empirical research provides evidence-based, action-oriented tools to startup founders and HR leaders to posture their organizations toward pro-societal and pro-innovation social value through diverse high-performance teams. The work demonstrates recruitment and retention with the purpose of social impact as inclusive systemic paradox and effect of impact within the startup ecosystem.